Expression, purification, and bioactivity of GST-fused v-Src from a bacterial expression system - 龚兴国 纪静 谢捷 周远 张俊彦 钟文涛 (Journal of Zhejiang University. B. Science, 2006)
v-Src is a non-receptor protein tyrosine kinase involved in many signal transduction pathways and closely related to the activation and development of cancers. We present here the expression, purification, and bioactivity of a GST （glutathione S-transferase）-fused v-Src from a bacterial expression system. Different culture conditions were examined in an isopropyl ,B-D-thiogalactopyranoside （IPTG）-regulated expression, and the fused protein was purified using GSH （glutathione） affinity chromatography. ELISA （enzyme-linked immunosorbent assay） was employed to determine the phosphorylation kinase activity of the GST-fused v-Src. This strategy seems to be more promising than the insect cell system or other eukaryotic systems employed in earlier Src expression.